Ataluren Pharmacokinetics in Healthy Japanese and Caucasian Subjects. Issue 2 (10th January 2019) - Kong, Ronald; Laskin, Oscar L.; Kaushik, Diksha; Jin, Fengbin; Ma, Jiyuan; McIntosh, Joseph; Souza, Marcio; Almstead, Neil
Abstract: To evaluate the potential for ethnicity‐related differences in ataluren pharmacokinetics (PK) and safety, a phase 1 single‐dose study was conducted in 48 healthy (24 Japanese and 24 Caucasian subjects), nonsmoking male volunteers who were equally divided into 3 cohorts of oral doses at 5, 10, and 20 mg/kg. Blood samples were collected until 48 hours postdose. PK results demonstrated rapid absorption of ataluren, with peak plasma levels (Cmax ) being attained between 0.875 and 2.5 hours after dosing. The mean Cmax and area under the concentration‐time curve (AUC(0‐last) ) increased with each increasing dose level in both Japanese and Caucasian subjects. Although the Cmax was similar across all subjects at each dose regardless of ethnicity, Japanese subjects had a mean AUC(0‐last) approximately 14% to 34% lower than that of Caucasian subjects across the 3 dose levels. This difference was likely due to the higher variability of AUC values in Caucasian subjects and the relatively small study population. In conclusion, similar ataluren PK profiles were observed in healthy Japanese and Caucasian subjects following single oral administration of ataluren at all dose levels.